2018
DOI: 10.1111/jfd.12884
|View full text |Cite
|
Sign up to set email alerts
|

Moritella viscosa in lumpfish (Cyclopterus lumpus) and Atlantic salmon (Salmo salar)

Abstract: Winter ulcer disease, caused by Moritella viscosa, is a significant problem in cold water salmonid farming, although the bacterium can infect and cause disease in a number of other fish species, such as lumpfish (Cyclopterus lumpus). Lumpfish are used as cleaner fish, to eat sea lice from Atlantic salmon (Salmo salar) in sea pens. It remains to be established whether M. viscosa can be transmitted between the fish species. In this study, we examined whether a salmon isolate of M. viscosa could infect and cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…At 98 dpi, R. salmoninarum was isolated from spleen, liver and headkidney of the high dose infected lumpfish which showed no external, internal and histopathological disease signs ( Figures 2C and 3 ). Similar to our results, M. viscosa was isolated from kidneys of non-symptomatic lumpfish at 27 days post bath challenge ( 30 ). This implies that lumpfish could be asymptomatic carriers for R. salmoninarum , and chronic infection could be a common strategy of marine bacterial pathogens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…At 98 dpi, R. salmoninarum was isolated from spleen, liver and headkidney of the high dose infected lumpfish which showed no external, internal and histopathological disease signs ( Figures 2C and 3 ). Similar to our results, M. viscosa was isolated from kidneys of non-symptomatic lumpfish at 27 days post bath challenge ( 30 ). This implies that lumpfish could be asymptomatic carriers for R. salmoninarum , and chronic infection could be a common strategy of marine bacterial pathogens.…”
Section: Discussionsupporting
confidence: 88%
“…( 29 ) confirmed the experimental transmission of amoebic parasite from lumpfish to salmon ( 29 ). Also, Atlantic salmon susceptibility to a lumpfish isolate of M. viscosa reflecting the disease risk to salmon ( 30 ). Although BKD episodes have not been reported in lumpfish, its susceptibility and immune response to R. salmoninarum are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. viscosa infection was suggested to be initiated from both skin and gill of Atlantic salmon 11 , and the pathogenic mechanism of this bacterium in salmonid cells is delivered through cytoskeleton disruption, pore formation and lytic processes 12 . In addition to Atlantic salmon and rainbow trout ( Oncorhynchus mykiss ) 13 , M. viscosa may infect Atlantic cod ( Gadus morhua ), halibut ( Hippoglossus hippoglossus ) 14 , turbot ( Scophthalmus maximus ) 15 and lumpfish ( Cyclopterus lumpus ) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Haugland et al (29) confirmed the experimental transmission of amoebic parasite from lumpfish to salmon (29). Also, Atlantic salmon susceptibility to a lumpfish isolate of M. viscosa reflecting the disease risk to salmon (30). Although BKD episodes have not been reported in lumpfish, its susceptibility and immune response to R. salmoninarum are unknown.…”
Section: Discussionmentioning
confidence: 92%